A discussion on the training method of 109C forward somersault in platform diving - Jing, Q. (China Sport Science and Technology, 2004)
109C fornd forward somersault in plattform diving is a movement w ith hig h dif ficulty. However, modern diving training methods takes the advantage of land and pool protective belts combining the basic technique and capability in guide exercises and solves such problems as multi somersault and body opening technique in high platfo rm diving .